Pelaksanaan Pemberdayaan Masyarakat dalam Program Mayajuwita di Kota Blitar - Fadhila Ayu Ratnasari; Arie Ambarwati (Policy and Maritime Review, 2022)
This research is motivated by the importance of optimizing the implementation of community empowerment in a program so that it runs in accordance with the policy implementation plans that have been written and compiled. The implementation of the MAYAJUWITA program is regulated by Perwali No. 2 of 2016 concerning the implementing guidelines for community programs towards a tourism city (MAYAJUWITA). This implementation is proven to run with the attention and detailed implementation of the Government as a whole. This study uses a qualitative descriptive method with data collection techniques using observation, interviews, and documentation studies. The data processing technique uses data reduction, data presentation, drawing conclusions/verification. Research Results The implementation of community empowerment in the MAYAJUWITA program in Blitar City was able to run well because the sub-districts and villages of each Blitar City were able to optimize implementing regulations with the budget provided by the APBD PRO RAKYAT